Validation and Classification of Atypical Splicing Variants Associated With Osteogenesis Imperfecta - Li, Lulu; Cao, Yixuan; Zhao, Feiyue; Mao, Bin; Ren, Xiuzhi; Wang, Yanzhou; Guan, Yun; You, Yi; Li, Shan; Yang, Tao; Zhao, Xiuli (Frontiers in Genetics, 2019)
Osteogenesis Imperfecta (OI) is a rare inherited bone dysplasia, which is mainly caused by mutations in genes encoding type I collagen including COL1A1 and COL1A2. It has been well established to identify the classical variants as well as consensus splicing-site-variants in these genes in our previous studies. However, functional examination of whether the atypical variants affect splicing in the OI patients is limited. Here we collected blood samples from 34 patients carrying the variants that are located close to splice donor/acceptor sites in either COL1A1 or COL1A2 from a cohort of 867 OI patients. Minigene splicing assay and sequencing analysis were conducted. We found 19 of 34 variants led to aberrant splicing effects, while 15 without remarkable aberrant splicing effect. Among the 19 affected splicing, 16 variants led to single splicing influence: 10 led to solely exon skipping, 2 only resulted in truncated exon, and 4 only resulted in intron retention. Interestingly, there were some complicated cases (n=3) that more than one mutant transcripts were found caused by recognition of several different splice sites. This study expands our knowledge of atypical splicing variants, and emphasize the importance to classify the splicing effect for variants near exon/intron boundaries.